1986
DOI: 10.1159/000212766
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and Small-Bowel Mucosa: A Morphometric Study

Abstract: A direct effect of ageing in reducing mucosal surface area of the small intestine is still disputed. The aim of this study was to morphometrically evaluate a panel of jejunal biopsy specimens obtained from 16 elderly patients and 22 younger controls, all complaining of abdominal symptoms but without evidence of malabsorption and/or malnutrition in either group. Quantitative histology was performed by calculating the surface area to volume ratio of jejunal mucosa and the mean enterocyte height. The mean of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…Based upon older studies, there is the misconception that small intestinal villus height and surface area are reduced compared with that in young controls. However, careful evaluation of jejunal biopsy specimens from healthy elderly volunteers shows that the anatomy of epithelial cells and the surface area does not differ from that found in the young [1] . In the rat, although villus cell numbers in the proximal small intestine are similar in the young and old, crypt cell numbers are greater in Fischer 344 rats over age 24 months [2] accompanied by increased epithelial cell proliferation [3] and altered controls of cell production [4] .…”
Section: Structural and Functional Changes In The Small Intestinementioning
confidence: 89%
“…Based upon older studies, there is the misconception that small intestinal villus height and surface area are reduced compared with that in young controls. However, careful evaluation of jejunal biopsy specimens from healthy elderly volunteers shows that the anatomy of epithelial cells and the surface area does not differ from that found in the young [1] . In the rat, although villus cell numbers in the proximal small intestine are similar in the young and old, crypt cell numbers are greater in Fischer 344 rats over age 24 months [2] accompanied by increased epithelial cell proliferation [3] and altered controls of cell production [4] .…”
Section: Structural and Functional Changes In The Small Intestinementioning
confidence: 89%
“…Although earlier studies reported significant apparently age-related effects including reduced gastric acid secretion [37,38] and gastric emptying [39], reduced splanchnic blood flow [40], and absorptive capacity of the small intestine [41], probably due to the effects of disease states, more recent reports have not confirmed these findings in healthy subjects [23,25,42,43].…”
Section: Drug Absorptionmentioning
confidence: 90%
“…Careful morphometric studies agree that ageing in humans is not associated with a reduction in the extent of the absorptive area [1,2]. This preservation of normal morphology seems to be due to an increased enterocyte turnover and to an expansion of the proliferative zone of small intestinal mucosa [3].…”
Section: Introductionmentioning
confidence: 90%